Surgical management of chronic pelvic instability following periacetabular osteotomy nonunion. Issue 6 (November 2020) - Shearman, Alexander D; Hashemi-Nejad, Aresh; Bankes, Marcus JK; Lewis, Angus D
Introduction: Periacetabular osteotomy (PAO) is an established treatment for symptomatic acetabular dysplasia in skeletally mature individuals without arthritis. Pelvic nonunion and associated stress fractures are under-reported. Nonunited stress fractures can cause continued buttock pain and pelvic instability. The aim of this study is to report on our experience managing patients with ongoing pain following nonunion of PAO. Patients and methods: 8 patients presented to a tertiary referral pelvic service with symptomatic PAO nonunion between 2015-2018. All patients underwent open reduction internal fixation of the superior pubic ramus nonunion, with ipsilateral iliac autograft, at an average of 48.1 (15–82) months following initial osteotomy. Demographic and perioperative data were recorded. Follow-up was on average to 9.9 months, once union was confirmed radiographically. Results: All patients were female and average age was 31.8 (18–41) years. In 7/8 (87.5%) patients a modified Stoppa approach was successfully utilised. 1 patient required an ilioinguinal approach due to the amount of rotational correction. All patients went on to union at the superior pubic ramus and reported improvement in mechanical symptoms. 5/8 (62.5%) patients were noted to develop union of the posterior column or inferior pubic ramus stress fracture indirectly. 2/8 (25%) patients developed progression of intra-articular pain, despite restoration of pelvic stability. 1 patient required intraoperative transfusion due to femoral vein injury. There were no other complications seen in this series. Conclusions: To our knowledge, this is the largest case series of surgically managed PAO nonunion. Pelvic instability resulting from nonunion and stress fracture can be satisfactorily addressed by mobilising, grafting and plating the nonunion at the superior pubic ramus. The modified Stoppa approach is suitable in most cases, allowing excellent exposure whilst minimising the insult to soft tissues. The altered anatomy of the pelvis following PAO should be anticipated to reduce the risk to nearby neurovascular structures.